Effects of physical exercise on postural alteration and functionality of elderly people: care on healthy longevity (Research, Society and Development, 2020)
An interventionist approach research, aimed to evaluate the effects of physical exercise on postural alteration and functional condition of six elderly people,  participants in an interdisciplinary nucleus of research and extension, included by presenting postural alteration, rheumatic issues, Systemic Atrial Hypertension (HAS) and/or type 2 Diabetes Mellitus (DM2). Adopted the Postural Evaluation Tool (IAP); Symmetrograph; Analog Evaluation Scale (EVA); semi-structured interview and kinesiotherapeutic protocol, adapted to the research, implemented in three weekly sessions, sixty minutes each session in alternate days, 25 sessions in total. Results: comparing to the previous IAP, there was a 66% to 33% reduction in head rotation; improvement in iliac crests alignment from 50% to 66%; improvement in valgus knee from 33% to 16%. For side view: forward leaning head reduction form 66% to 33%; protruding shoulder reduction from 66% to 33%. Pain relieving in EVA was very significative for five of the six participants plus, HAS and DM2 with an outstanding 100% reduction. In conclusion, the proximal care approach contributed to the participants’s health improvement, potentialized adhesion of regular physical activities  in the nucleus and reverted itself to acquisition of benefits, from the healthy living process to longevity.